Foix-Chavany-Marie Syndrome due to Unilateral Anterior Opercular Damage with Contralateral Infarction of Corona Radiata - Yoshii, Fumihito (Case Rep Neurol, 2019)
Foix-Chavany-Marie syndrome (FCMS) is a rare type of pseudobulbar palsy characterized by automatic-voluntary dissociation of movements of the face, tongue, pharynx, and masticatory muscles. Most cases are due to bilateral ischemic lesions of the anterior operculum, but the syndrome has also been described after unilateral opercular damage, either isolated or associated with contralateral cortico-nuclear tract involvement. We report a patient with FCMS due to right anterior opercular lesion with contralateral infarction of the corona radiata. The patient presented with paralysis of the face and tongue with automatic and voluntary dissociation. To our knowledge, FCMS with this peculiar lesion topography has rarely been reported. We discuss the underlying mechanism with reference to MRI and diffusion tensor imaging.